Efficacy of aquatic exercises on balance in children with sickle cell anemia: A randomized controlled trial - Omar Abd El-Hameed Abd El-Fattah Ghetas; Azza Abd El-Aziz Abd El-Hady; El-Sayed Ali Shaheen Ali; Amira El-Sayed El-Bagalaty (Sport TK, 2023)
The aim of this study was to investigate the efficacy of aquatic exercises on balance in children with sickle cell anemia. A randomized controlled trial was conducted. Sixty children with mild sickle cell anemia and poor balance from both sexes (35 boys and 25 girls) participated in this study. Their ages ranged from 5-10 years with a mean value of 7.30± 1.66 years in the study group (A) and 7.26 ±1.70 in the control group (B). They were divided into two equal groups: the study group (A) and the control group (B). The study group (A) consisted of 30 children (17 boys and 13 girls), who received medical treatment (prescribed by physician), balance exercises, and aquatic exercises sessions. The control group (B) consisted of 30 children (18 boys and 12 girls) who received medical treatment (prescribed by physician) and balance exercises only. The program continued for eight weeks with two sessions per week with a total of sixteen sessions. Each session lasted forty minutes for aquatic exercises sessions and thirty minutes for the balance exercises sessions. Balance was measured before and after treatment using the Pediatric Balance Scale (PBS). A complete blood analysis was performed before and after treatment. The balance functions showed a statistically significant improvement in the study group (A) (p < 0.05) with an improvement of 28.09% after treatment, while in the control group (B) the improvement was not statistically significant (p > 0.05) with a percentage of 10.93% after treatment. The mean Hb value also improved by 29.2% in the study group (A) with a statistically significant increase (p < 0.05), while in the control group (B) there was no statistically significant improvement (p > 0.05) with a percentage of 8.44% after treatment. The aquatic exercise program has a positive effect on improving balance functions in children with sickle cell anemia.